2016
DOI: 10.1007/s12640-015-9595-z
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection Promoted by Guanosine Depends on Glutamine Synthetase and Glutamate Transporters Activity in Hippocampal Slices Subjected to Oxygen/Glucose Deprivation

Abstract: Guanosine (GUO) has been shown to act as a neuroprotective agent against glutamatergic excitotoxicity by increasing glutamate uptake and decreasing its release. In this study, a putative effect of GUO action on glutamate transporters activity modulation was assessed in hippocampal slices subjected to oxygen and glucose deprivation (OGD), an in vitro model of brain ischemia. Slices subjected to OGD showed increased excitatory amino acids release (measured by D-[(3)H]aspartate release) that was prevented in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 50 publications
2
18
1
Order By: Relevance
“…Particularly, we suggest that NO and ONOO − production are more responsive to nNOS inhibition than eNOS or iNOS in this in vitro ischemia model in hippocampal slices. Guanosine plays a significant role in the defense mechanisms against cerebral ischemia by inducing key cellular functions in this injury situation, as K + channels activation [14], glutamate uptake increase, reduction of inflammatory mediators expression [15,33], and, as firstly shown in this study, reduction of NO and ONOO − production similarly to NOS inhibitors. Although the exact mechanism exerted by GUO on the NO production system is still not completely understood, we reinforce the hypothesis that GUO could be used to devise new strategies for stroke treatment.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Particularly, we suggest that NO and ONOO − production are more responsive to nNOS inhibition than eNOS or iNOS in this in vitro ischemia model in hippocampal slices. Guanosine plays a significant role in the defense mechanisms against cerebral ischemia by inducing key cellular functions in this injury situation, as K + channels activation [14], glutamate uptake increase, reduction of inflammatory mediators expression [15,33], and, as firstly shown in this study, reduction of NO and ONOO − production similarly to NOS inhibitors. Although the exact mechanism exerted by GUO on the NO production system is still not completely understood, we reinforce the hypothesis that GUO could be used to devise new strategies for stroke treatment.…”
Section: Discussionsupporting
confidence: 67%
“…In previous studies from our group, the neuroprotective effect of GUO was shown in hippocampal slices subjected to the OGD/reoxygenation protocol. GUO prevents the decrease in cell viability, by increasing glutamate uptake and glutamine synthetase activity, decreasing glutamate release, ROS production and inflammatory mediators expression, including reduction of iNOS expression [14,15,33,40]. The exact interaction site of GUO in cellular membranes is still unknown, although it has been suggested [41,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that neuroprotective effects of GUO depend on glutamatergic system modulation, through increasing glutamate uptake or decreasing glutamate release, that may be responsible for increasing glutamine synthetase (GS) activity [13,14,16,18,40,41]. Despite all of this evidence, we did not observe GUO effects on glutamate uptake, release, or GS activity, an enzyme that had been considered as a negative growth regulator in glioma cells [42].…”
Section: Discussioncontrasting
confidence: 63%
“…Similarly, upon excitotoxicity and oxidative stress a failure of cellular bioenergetics occurs [4]. Importantly, a neuroprotective role of guanosine has been extensively investigated in animal and cellular models of ischemia, excitotoxicity and oxidative stress [5][6][7][8][9][10]. Indeed, we have demonstrated that guanosine prevents reactive oxygen species (ROS) generation and cell death in hippocampal slices subjected to the oxygen/glucose deprivation (OGD) [11].…”
Section: Introductionmentioning
confidence: 99%